Genetic Mapping and Discovery of the Candidate Gene for Black Seed Coat Color in Watermelon (Citrullus lanatus) - Li, Bingbing; Lu, Xuqiang; Gebremeskel, Haileslassie; Zhao, Shengjie; He, Nan; Yuan, Pingli; Gong, Chengsheng; Mohammed, Umer; Liu, Wenge (Frontiers in Plant Science, 2020)
Seed coat color is an important trait highly affecting the seed quality and flesh appearance of watermelon (Citrullus lanatus). However, the molecular regulation mechanism of seed coat color in watermelon is still unclear. In the present study, genetic analysis was performed by evaluating F1, F2 and BC1 populations derived from two parental lines (9904 with light yellow seeds and Handel with black seeds), suggesting that a single dominant gene controls the black seed coat. The initial mapping result revealed a region of interest spanning 370 kb on chromosome 3. Genetic mapping with CAPS and SNP markers narrowed down the candidate region to 70.2 kb. Sequence alignment of the three putative genes in the candidate region suggested that there was a single-nucleotide insertion in the coding region of Cla019481 in 9904, resulting in a frameshift mutation and premature stop codon. The results indicated that Cla019481 named ClCS1 was the candidate gene for black seed coat color in watermelon. In addition, gene annotation revealed that Cla019481 encoded a polyphenol oxidase (PPO), which involved in the oxidation step of the melanin biosynthesis. This research finding will facilitate maker-assisted selection in watermelon and provide evidence for the study of black seed coat coloration in plants.